"Homozygous, and compound heterozygous mutation in 3 Turkish family with Jervell and Lange-Nielsen syndrome: case reports" - Fahrettin Uysal; Burcu Turkgenc; Guven Toksoy; Ozlem M. Bostan; Elif Evke; Oya Uyguner; Cengiz Yakicier; Hulya Kayserili; Ergun Cil; Sehime G. Temel (BMC, 2017)
Abstract Background Jervell and Lange-Nielsen syndrome (JLNS) isa recessive model of long QT syndrome which might also be related to possible hearing loss. Although the syndrome has been demonstrated to be originated from homozygous or compound heterozygous mutations in either the KCNQ1 or KCNE1 genes, additional mutations in other genetic loci should be considered, particularly in malignant course patients. Case presentations Three patients were admitted into hospital due to recurrent seizures/syncope, intrauterine and postnatal bradycardia respectively; moreover all three patients had congenital sensorineural hearing-loss. Their electrocardiograms showed markedly prolonged QT interval. Implantable defibrillator was implanted and left cardiac sympathetic denervation was performed due to the progressive disease in case 1. She had countless ventricular fibrillation and appropriate shock while using an implantable defibrillator. The DNA sequencing analysis of the KCNQ1 gene disclosed a homozygous c.728G > A (p.Arg243His) missense mutation in case1. Further targeted next generation sequencing of cardiac panel comprising 68 gene revealed a heterozygous c.1346 T > G (p.Ile449Arg) variant in RYR2 gene and a heterozygous c.809G > A (p.Cys270Tyr) variant in NKX2-5 gene in the same patient. Additional gene alterations in RYR2 and NKX2-5 genes were thought to be responsible for progressive and malignant course of the disease. As a result of DNA sequencing analysis of KCNQ1 and KCNE1 genes, a compound heterozygosity for two mutations had been detected in KCNQ1 gene in case 2: a maternally derived c.477 + 1G > A splice site mutation and a paternally derived c.520C > T (p.Arg174Cys) missense mutation. Sanger sequencing of KCNQ1 and KCNE1 genes displayed a homozygous c.1097G > A (p.Arg366Gln) mutation in KCNQ1 gene in case 3. β-blocker therapy was initiated to all the index subjects. Conclusions Three families of JLNS who presented with long QT and deafness and who carry homozygous, or compound heterozygous mutation in KCNQ1 gene were presented in this report. It was emphasized that broad targeted cardiac panels may be useful to predict the outcome especially in patients with unexplained phenotype-genotype correlation. Clinical presentations and molecular findings will be discussed further to clarify the phenotype genotype associations.